2021
DOI: 10.1111/1477-8947.12241
|View full text |Cite
|
Sign up to set email alerts
|

Nepal's hydropower development: Predicament and dilemma in policy‐making

Abstract: Nepal, the world's second most water‐rich country, nevertheless struggles to provide sufficient domestic electricity. Despite Nepal's potential to become the hydropower source for South Asia, it still relies heavily on importing electricity from India. This paper investigates why Nepal's hydropower capacity is inadequately utilized from both domestic and international perspectives and finds that domestic factors such as geo‐climate features, weak infrastructure, political instability, and institutional deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In addition, the ecological aspects: margin principles (defined by 1993 EIA parameters [ 47 ]) and release rates (defined by the Water Resources Development Policy 2001) have been rigidly instituted, making it unfeasible for application to every type of hydropower project. This has also led to partial access and less usage of electricity, especially in rural areas [ 48 ].…”
Section: Barriers and Constraints For Hydropower Developmentmentioning
confidence: 99%
“…In addition, the ecological aspects: margin principles (defined by 1993 EIA parameters [ 47 ]) and release rates (defined by the Water Resources Development Policy 2001) have been rigidly instituted, making it unfeasible for application to every type of hydropower project. This has also led to partial access and less usage of electricity, especially in rural areas [ 48 ].…”
Section: Barriers and Constraints For Hydropower Developmentmentioning
confidence: 99%
“…Nepal with its rich freshwater resources (WECS, 2011) has tremendous potential for hydropower generation, agriculture and irrigation; aquatic biodiversity, fishery and aquaculture (ADB, 2018). Studies have suggested that the country has the hydropower potential of generating 83,000 MW (Zou et al, 2021). However, only an estimated 15 (BCM) billion cubic meters is reported to be in use out of 225 BCM available surface water.…”
Section: Introductionmentioning
confidence: 99%